2017
DOI: 10.1080/01612840.2016.1253807
|View full text |Cite
|
Sign up to set email alerts
|

Violent Crime in the Lives of Homeless Female Ex-Offenders

Abstract: The cyclical pattern of violence in the lives of homeless female ex-offenders may precipitate ongoing substance use and recidivism – all of which have shown to be mounting public health issues affecting successful reentry. This paper which analyzed baseline data from a longitudinal study of 126 female ex-offenders in Los Angeles and Pomona, California, highlighted the factors found to be associated with violent crime among homeless female ex-offenders. A multiple logistic regression model for whether or not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…HFOs transitioning into the community are at a vulnerable crossroads whereby there is a high risk of recidivism and low risk of success sustaining the community transition. Informed by our previous research with this community (Nyamathi et al, 2017; Salem, Nyamathi, Keenan, et al, 2013), the current study has shown early promise at mitigating recidivism at six months. Building upon these findings will necessitate integrating MI into the DBT intervention to address desire for help and to gain a greater understanding of differences which influence recidivism among younger versus older women during reentry.…”
Section: Discussionmentioning
confidence: 81%
“…HFOs transitioning into the community are at a vulnerable crossroads whereby there is a high risk of recidivism and low risk of success sustaining the community transition. Informed by our previous research with this community (Nyamathi et al, 2017; Salem, Nyamathi, Keenan, et al, 2013), the current study has shown early promise at mitigating recidivism at six months. Building upon these findings will necessitate integrating MI into the DBT intervention to address desire for help and to gain a greater understanding of differences which influence recidivism among younger versus older women during reentry.…”
Section: Discussionmentioning
confidence: 81%
“…Women emerging from jails and prisons are more likely to experience homelessness than formerly incarcerated men, at a rate of 264 per 10,000 vs. 195 per 10,000 [ 14 ]. Unhoused women with histories of incarceration also have significantly higher histories of physical, sexual, and injurious assault from intimate and non-intimate sexual partners across the course of their life, along with co-occurring substance use disorders [ 17 ]. Without secure housing, recently released women are also at increased risk of relapsing into addiction [ 18 ] and IPV [ 19 ].…”
Section: Introductionmentioning
confidence: 99%